Inflammatory Links Between High Fat Diets and Diseases - Duan, Yehui; Zeng, Liming; Zheng, Changbing; Song, Bo; Li, Fengna; Kong, Xiangfeng; Xu, Kang (Frontiers in Immunology, 2018)
In recent years, chronic overnutrition, such as consumption of a high-fat diet (HFD), has been increasingly viewed as a significant modifiable risk factor for diseases such as diabetes and certain types of cancer. However, the mechanisms by which HFDs exert adverse effects on human health remains poorly understood. Here, this paper will review the recent scientific literature about HFD-induced inflammation and subsequent development of diseases and cancer, with an emphasis on mechanisms involved. Given the expanding global epidemic of excessive HFD intake, understanding the impacts of a HFD on these medical conditions, gaining great insights into possible underlying mechanisms, and developing effective therapeutic strategies are of great importance.